Adaptive performance scale: Translation and validation in English and Dutch - Krijgsheld, Marcel; Tummers, Lars (L.G.); Scheepers, Floortje (F.E.) (Human Factors in Healthcare (Online), 2024)
The significance of adaptive performance in today's rapidly evolving work environment cannot be overlooked. Despite its crucial nature, no validated scale exists for assessing adaptive performance in either English or Dutch. This project aims to rectify this deficiency by providing researchers with a reliable and validated instrument to measure adaptive performance. The French scale was translated into English and Dutch using forward and backward translation techniques and was pretested by healthcare professionals. A uniform interpretation of the translations was achieved, and the final questionnaires were distributed to healthcare professionals. We explored the dimensionality of the scales using factor analysis and tested for reliability and validity. Questionnaires were completed by 283 English-speaking and 306 Dutch-speaking respondents. Both questionnaires demonstrated good internal consistency (Cronbach's alpha 0.87) and convergent and discriminant validity. Minor issues were addressed. This analysis presents a dependable and legitimate tool for the further exploration of adaptive performance. The primary focus of this project was on healthcare professionals. Given that the original scale was evaluated across various occupations and the items were worded in general terms, the scale could be applied generally. This project successfully addressed the need for a scale on adaptive performance for researchers conducting studies with English or Dutch respondents.